2022
DOI: 10.3390/buildings12030324
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to BIM-Based Life Cycle Sustainability Assessment for Buildings: An Interpretive Structural Modelling Approach

Abstract: With the emergence of Building Information Modelling (BIM) as central to construction design, planning, execution and maintenance, integration into the entire infrastructure sustainability process is imperative for achieving sustainable development. Despite its immense benefit of aiding compliance to sustainable construction, potential barriers continue to widen the gap in implementation. Therefore, this study adopts the “interpretive structural modelling approach” to advance a ranked structure of the interrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The examination of the identified barriers compared with the results of the literature review revealed many similarities. Barriers related to resources and cost (G2) [36,49,55,62,63], skills and knowledge (G3) [9,21,29,31], human behaviour (G5) [44,49,55], and governmental (G7) [21,31,49] were all identified previously from similar studies in the literature review, as shown in Table 1. Other barriers were mentioned by participants and were found to be related to the wood industry in particular, such as interoperability issues [46,64] and insufficient object libraries (G1) [50].…”
Section: Comparison Between Gt Results and Literature Review Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The examination of the identified barriers compared with the results of the literature review revealed many similarities. Barriers related to resources and cost (G2) [36,49,55,62,63], skills and knowledge (G3) [9,21,29,31], human behaviour (G5) [44,49,55], and governmental (G7) [21,31,49] were all identified previously from similar studies in the literature review, as shown in Table 1. Other barriers were mentioned by participants and were found to be related to the wood industry in particular, such as interoperability issues [46,64] and insufficient object libraries (G1) [50].…”
Section: Comparison Between Gt Results and Literature Review Resultsmentioning
confidence: 85%
“…Only one paper was found that investigates the current use, barriers, and driving forces of BIM implementation among mid-sized contractors. The authors concluded in their study that the main barriers are a lack of demand from clients and the absence of internal demand in companies [49]. Furthermore, the literature review conducted in this study revealed that there is a lack of interest in exploring BIM implementation barriers that are hindering the expansion of BIM implementation in the wood construction industry in general and in Sweden specifically.…”
Section: Bim Implementation Barriersmentioning
confidence: 86%
See 1 more Smart Citation
“…An external questionnaire design and Table A-2. An internal questionnaire design adapted from [46]; and interviews with the objective of acquiring additional data. Since each interview is conducted independently, this method typically produces results with a sample size that is quite tiny.…”
Section: Collecting Datamentioning
confidence: 99%
“…The main advantages of ISM include incorporating experts' opinions based on their knowledge and experience, allowing amending opinions and altering the evaluations without demanding too many operations to evaluate the systems with less than 15 variables, making it suitable to analyze real-life conditions [46,54]. Researchers frequently use this method in ordering and decomposing complex relationships between barriers to adopting innovations in construction [21,[55][56][57][58][59][60].…”
Section: Stage Ii: Ism Modelmentioning
confidence: 99%